Mechanical property improvement of a AA6082 alloy by the TV-CAP process as a novel SPD method - KENTLİ, AYKUT (My University, 2023)
© 2023 Walter de Gruyter GmbH, Berlin/Boston.Twisted variable channel angular pressing (TV-CAP) is a novel method. While it combines the advantages of equal channel angular pressing (ECAP), twist extrusion and direct extrusions, also it eliminates the disadvantages of these methods. Finite element analysis was also carried out in order to examine the design parameters, material flow and examine the effective strain values. Hardness and tensile tests were performed to examine the effect of TV-CAP on the mechanical properties of AA6082. In addition, optic microscope, SEM and TEM images were taken respectively and XRD, EDS and EBSD analyses were accomplished in order to investigate the microstructural analysis. As a result of this study, it has been observed that the material has hardened approximately 3 times compared to the annealed material and became 1.5 times stronger in terms of ultimate tensile strength. It was also concluded that, this new method is more efficient than twist extrusion and multi-pass equal channel angular pressing processes.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MALZEME BİLİMİ, KOMPOZİTLER; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENGINEERING, MECHANICAL; MATERIALS SCIENCE, COMPOSITES; Genel Malzeme Bilimi; Fizik Bilimleri; Malzemelerin mekaniği; Makine Mühendisliği; General Materials Science; Physical Sciences; Mechanics of Materials; Mechanical Engineering; AA6082; equal channel angular pressing; mechanical properties; severe plastic deformation; TV-CAP; twist extrusion